High prevalence of post COVID-19 fatigue in patients with type 2 diabetes: A case-control study. Issue 6 (November 2021) - Mittal, Juhi; Ghosh, Amerta; Bhatt, Surya Prakash; Anoop, Shajith; Ansari, Irshad Ahmad; Misra, Anoop
Abstract: Background: Post COVID-19 syndrome (PCS) has emerged as a major roadblock in the recovery of patients infected with SARS-CoV-2. Amongst many symptoms like myalgia, headache, cough, breathlessness; fatigue is is most prevalent and makes the patient severely debilitated. Research on PCS, in particular fatigue, in patients with diabetes has not been done. Methodology: In this prospective study, we included patients with type 2 diabetes (T2D) who had COVID-19 (mild to moderate severity), and matched T2D patients who did not suffer from COVID-19. Demography, anthropometry, glycemic measures, treatment, and details of COVID-19 were recorded. Symptoms were scored using Chalder Fatigue Scale (reported as fatigue score, FS) and handgrip strength (in kg) was recorded by Jamar Hydraulic Hand Dynamometer. Results: A total of 108 patients were included (cases, 52, controls, 56). Both groups were matched for age, duration of diabetes, BMI, TSH, serum albumin and vitamin D levels. T2D patients who had COVID-19 showed significantly more fatigue when compared with patients who did not have COVID-19 but both groups had comparable handgrip strength. Furthermore, patients with T2D with previous COVID-19 infection and who had FS > 4 have had significant higher inflammation markers during acute illness, and post COVID-19, had increased post prandial blood glucose levels, lost more weight, had reduced physical activity and showed significantly lower handgrip strength as compared to those with FS < 4. Conclusion: Patients with T2D who had COVID-19 infection as compared to those without had significantly more fatigue after the acute illness, and those with higher FS had reduced handgrip strength indicating sarcopenia, even after careful matching for common contributory factors to fatigue at baseline. Rehabilitation of those with FS>4 after acute infection would require careful attention to nutrition, glycemic control and graduated physical activity protocol. Highlights: We compared patients with T2D who had COVID-19 infection, and matched T2D patients who did not suffer from COVID-19 infection. Patient with T2D who had COVID-19 infection had significantly more fatigue, weight loss and reduced exercise capacity, but showed preserved handgrip strength. Patients with T2D and COVID-19 having higher fatigue had loss of weight, high inflammatory markers and reduced handgrip strength.